Multiletramentos no livro didático: análise de uma coleção de língua inglesa para o ensino médio - Tôrres Neto, Agápito Pereira (Universidade Federal Rural do Semi-Árido, 2019)
The studies on multiliteracies bring important contributions to the teaching of languages and the premises of this pedagogy are present on the oficial documents of Brazilian education that guide the teaching and learning practices and the production of textbooks to public schools in what refers the teaching-learning theories. Thus, the research presented here aims to analyze how reading and text production activities on the textbooks collection “Way to go!” designed to the Secondary Education may contribute to the development of multiliteracies' practices in the teaching of English. The analysis of textbooks is considered relevant and important, since this material is present in every public school of Brazil, presenting (or not) contributions to an efficient and meaningful language teaching. The theoretical background of this research is based on the works of the New London Group (1996), Soares (1998); Kleiman (1995); Rojo (2009); Rojo, Moura (2012). In what refers to the multiliteracies; Paiva (2015); PNLD (2018), considering the aspects of language teaching; Moita Lopes (1996); Leffa (1988), when considering works that deal with the study of textbooks; and, finally Bakhtin (2011); Dionísio (2007); Marcuschi (2008), that discuss about the speech genres. Since this study is related to the teaching of languages in Brazil, official documents such as the National Curriculum Guidelines, the National Curriculum Parameters for Secondary Education and the National Common Curricular Base, Brazil (2000; 2002; 2006, 2017) were studied, as well as Brazil (1998, 1999) on the challenges of English teaching in Brazil, among others. This is a documentary research and its universe is the textbook collection “Way to go!” designed to the Secondary Education. The corpus is formed by the reading and text production activities. The collection that counts with three volumes was part of the Textbook Guide in 2018, giving to the teachers of the whole country the opportunity to choose the English textbook for Secondary Education. The data, in analysis, show how the textbooks integrate the pedagogy of multiliteracies through reading and text production activities and how this can contribute to the development of multiliteracies’ practices and the integral human development of students from public education. The analysis, made from clippings taken from the sections related to reading activities and text production present in all units of the 3 volumes that make up the collection, reveals the presence of proposals that encourage the of multiliteracies' practices by highlighting the categories: multicultural and multimodal. The 6 sections analyzed: Before Reading, Reading, Reading for general comprehension, Reading for detailed comprehension, Reading for critical thinking, and Writing. They bring aspects that favor the work on multiculturalism: racial aspects, point of view or criticism, type of information and vocabulary; as well as offering proposals for work on multimodality: use of colors and images, graphic effects, information structure, criticality in the choice of discourse genres.
Keywords: Multiletramentos; Livros didáticos; Língua inglesa; Ensino médio; Multiliteracies; Textbooks; English language; Secondary education12z; MULTIDISCIPLINAR::ENSINO